Hypoxia-activated small molecule-induced gene expression - Collins, S; Saha, J; Bouchez, L; Hammond, E; Conway, S (American Chemical Society, 2018)
Hypoxia, a condition of reduced oxygen, occurs in a wide variety of biological contexts, including solid tumors and bacterial biofilms, which are relevant to human health. Consequently, the development of chemical tools to study hypoxia is vital. Here we report a hypoxia-activated, small-molecule-mediated gene expression system using a bioreductive prodrug of the inducer isopropyl 1-thio-β-d-galactopyranoside. As a proof-of-concept we have placed the production of a green fluorescent protein under the control of hypoxia. Our system has the potential to be extended to regulate the production of any given protein of choice.